Needle Aspiration in Tuberculosis-Associated Secondary Spontaneous Pneumothorax - Candrawati, Ni Wayan; Indraswari, Putu Gita; Komalasari, Ni Luh Gede Yoni (Jurnal Respirasi, 2024)
Introduction: The management of tuberculosis-associated secondary spontaneous pneumothorax mostly requires chest tube insertion for complete drainage and resolution. We reported a case of tuberculosis-associated secondary spontaneous pneumothorax that improved with needle aspiration. Case: A 29-year-old female with pulmonary tuberculosis presented with sudden onset shortness of breath. Chest examination revealed asymmetry, decreased vocal fremitus, hypersonor, and decreased vesicular sound in the right lung field. Chest radiograph showed right pneumothorax with a 2 cm intrapleural distance. Needle aspiration was performed because the patient refused chest tube insertion. The first needle aspiration evacuated approximately 615 cc of air. The second needle aspiration was repeated 24 hours later due to clinical deterioration, and 610 cc of air was evacuated. Chest radiograph evaluation on the 6th day of treatment showed no pneumothorax. During hospitalization, the patient received oxygen therapy, anti-tuberculosis drugs, chest physiotherapy, and other symptomatic therapies such as mucolytics. The patient's condition improved, and she was discharged on the 9th day of hospitalization. Tuberculosis-associated secondary pneumothorax occurs in 1-3% of cases. Conclusion: Needle aspiration is a therapeutic modality for tuberculosis-associated secondary spontaneous pneumothorax. This modality has several advantages, including shorter length of stay, less cost and pain, and fewer complications. Needle aspiration combined with oxygen therapy, anti-tuberculosis drugs, and chest physiotherapy should be the modality of treatment for tuberculosis-associated secondary pneumothorax.